THE EFFECT OF SALES PROMOTION AND MOBILE MARKETING ON PURCHASE OF BAKSO MARGANA BRANCH MAP NUMBER 91 POST COVID-19 - Rachmad Aditya Suparto; Nuslih Jamiat (SEAN Institute, 2023)
The purpose of this study was to find out how much influence sales promotion and mobile marketing have on purchasing decisions at Bakso Margana Restaurant, Jalan Peta No. 91 branch. The method used in this research is a quantitative method with a descriptive research type. The population used in this study were consumers who had bought Bakso Margana Restaurant products, Jalan Peta No. 91, aged 34-45 years with a sample size of 100 respondents. Sampling was used in this study, namely, the purposive sampling method. Based on the results of the study using descriptive analysis with the help of SPSS for Windows software, it shows that the Sales Promotion and Mobile Marketing variables are included in the very good category with no significant effect simultaneously and there is a partial effect on the Product Purchasing Decision of the Bakso Margana Restaurant, Jalan Peta No. 91.